Biomass and lipid production of marine diatom Chaetoceros ChTA at different nutrient concentrations - Liên, Nguyễn Thị Thu; Sơn, Nguyễn Hồng; Nhân, Lê Thị Tuyết (Vietnam Journal of Biotechnology, 2018)
Microalgae, especially diatom, are an optimal resource of polyunsaturated fatty acids (PUFAs). Recently, the new industrial scale culture systems are being developed for the purpose of producing the large amounts of biomass for biofuel, medicinal, cosmetical production. However, an economic utilization system needs to be standardized for the optimal production of the resources. In this way, manipulation of culture conditions (physicochemical factors) represents a solution to increase the lipid yield. The strain Chaetoceros ChTA is one of the high potential lipid strains, isolated from Thuan An coastal zone, Thua Thien Hue province. This paper deals with the growth and total lipid content of the marine diatom strain, Chaetoceros ChTA at different concentrations of sodium nitrate, sodium phosphate and sodium silicate under the laboratory condition. In addition, the fatty acid composition of the strain Chaetoceros ChTA growing in f/2 medium (control formula) was also analyzed. The result showed that this diatom strain successfully growed with maximum biomass production of 0.482g/L at the 112.50 mg/L of sodium nitrate meanwhile maximum total lipid content of 25.62% dry cell weight was recorded in the medium amended with 2.13 mg/L sodium phosphate. The fatty acid composition of this strain in f/2 medium (control) was analysed through GC-MS and the result showed that the saturated fatty acid content was 32.3% while the content of unsaturated fatty acid was 65.9% of the total fatty acid (TFA). The fatty acid composition also contains a significant amount of EPA (14.33%) and DHA is suitable for navigation use them as functional foods, pharmaceuticals and feed supplements for animals in aquaculture